DEVELOPING CREATIVE PROBLEM-SOLVING SKILLS THROUGH PSYCHOLOGICAL STRATEGIES IN PRIMARY EDUCATION - Gulyamova Nigina Azimovna (Research Focus International Scientific Journal, 2025)
This article explores the development of creative problem-solving (CPS) skills in primary education through the application of psychological strategies. Drawing on established theories from developmental and educational psychology, it examines how fostering creativity and critical thinking in young learners can be systematically integrated into the curriculum. The paper reviews literature on the nature of CPS, its core components (fluency, flexibility, originality, elaboration), and foundational psychological frameworks such as Vygotsky’s sociocultural theory and Piaget’s constructivism. It analyzes effective pedagogical strategies, including encouraging open-ended questions, promoting divergent thinking, creating supportive environments, and embedding authentic, interdisciplinary problem-solving tasks. The findings highlight that CPS is not an innate trait but a learnable skill that can be significantly enhanced through targeted interventions and a shift away from traditional, rote-learning pedagogies. However, challenges persist, including curriculum constraints, assessment difficulties, and the need for teacher training. The article concludes by emphasizing the critical role of primary education in nurturing these essential 21st-century skills, arguing that integrating psychological principles into teaching practices is vital for preparing children to become confident, adaptable, and innovative thinkers capable of navigating complex future challenges.